Larval Taxonomy and Distribution of Genus Hydropsyche (Trichoptera: Hydropsychidae) in Northwestern Algeria - Bemmoussat-Dekkak, Soumya; Abdellaoui-Hassaine, Karima; Sartori, Michel; Morse, John C.; Zamora-Muñoz, Carmen (Zootaxa, 2021)
The main purpose of our paper is to document genus Hydropsyche (Trichoptera: Hydropsychidae) in northwestern Algeria and to provide the larval descriptions of the species set. Larvae, pupae, and imagines were collected from 14 sampling sites over a five-year period (2014–2019). Eight Hydropsyche species have been identified, with Hydropsyche siltalai being a new record for Algeria and North Africa, and Hydropsyche pellucidula a new record for Algeria. A comparison of our checklist with those of the Moroccan Rif and Europe is provided, as well as the geographical distribution of each species. This Algerian Hydropsyche species revision provides precise and reliable taxonomic characters for distinguishing larvae of the species, and a taxonomic key is proposed for their identification. In addition, information regarding their distribution is included.